Relationship Between Lifestyle and Hypertension - Tambuwun, Semuel; Malo, Irgina Sofiani; Terok, Maria; Tangka, Jon; Kanine, Esrom; Alam, Syamsu (Jurnal Ilmiah Perawat Manado (Juiperdo), 2023)
Background: Lifestyle is a behavior related to a person's efforts to maintain health. an unhealthy lifestyle is a factor in the onset of hypertension in a person, a lifestyle that can lead to hypertension, namely diet, physical activity lacks exercise so that it greatly affects a person's health. Objective To determine whether there is a relationship between lifestyle and the incidence of hypertension based on literature review. Methods This study uses a type of literature review research, namely research in the form of a literature review using the results of previous research and textbooks or research journals. To obtain data that is in accordance with the topic, researchers conducted a search for national and international based journals with two databases, namely Google Scholar and Science direct. With the provisions of the journals searched, researchers obtained 6 journals used for literature review. Results Researchers found 6 articles and met the inclusion and eligibility criteria according to the topic regarding the relationship between lifestyle and the incidence of hypertension. Conclusion Based on the research results from the literature review of a total of 6 journals that meet the inclusion criteria, it is concluded that there is a relationship between an unhealthy lifestyle and degenerative disease, namely hypertension. Suggestions This literature review is expected to provide a reference in nursing interventions and add insight into knowledge in further research on the relationship between lifestyle and the incidence of hypertension.